2011
DOI: 10.1016/j.jtcvs.2010.08.032
|View full text |Cite
|
Sign up to set email alerts
|

An artificial nanoemulsion carrying paclitaxel decreases the transplant heart vascular disease: A study in a rabbit graft model

Abstract: LDE-paclitaxel improved posttransplantation injury to the grafted heart. The novel therapeutic approach for heart transplantation management validated here is thus a promising strategy to be explored in future clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
(36 reference statements)
0
20
0
5
Order By: Relevance
“…A more recent clinical study revealed that in heart transplants with very late rejection (> 7 years following transplantation), the presence of intravascular macrophages and donor specific antibodies are robust predictors of the development of more severe GVD [102]. Therapies effective in reducing GVD have also been shown to be associated with a significantly deceased macrophage infiltration [103,104]. These recent studies further confirmed that macrophages play a role in the pathogenesis of GVD.…”
Section: Macrophages In Gvdmentioning
confidence: 91%
“…A more recent clinical study revealed that in heart transplants with very late rejection (> 7 years following transplantation), the presence of intravascular macrophages and donor specific antibodies are robust predictors of the development of more severe GVD [102]. Therapies effective in reducing GVD have also been shown to be associated with a significantly deceased macrophage infiltration [103,104]. These recent studies further confirmed that macrophages play a role in the pathogenesis of GVD.…”
Section: Macrophages In Gvdmentioning
confidence: 91%
“…In animal studies, cholesterol-rich nanoemulsions (LDE) resembling LDL combined with paclitaxel (LDE-paclitaxel) injected intravenously were demonstrated to reduce intimal width and reduce destruction of the media [70]. This may be a promising strategy for further exploration in clinical studies.…”
Section: Future Trendsmentioning
confidence: 99%
“…LDE-paclitaxel treatment resulted in marked reduction of the stenosis of the grafts, width of the intima and destruction of the medium layer. It is remarkable that the treatment reduced sevenfold the macrophage invasion of the myocardium, which is a landmark of organ rejection [92].…”
Section: Doxorubicin (Anthracycline)mentioning
confidence: 99%